STUDENTS’ MASTERY OF SYSTEMIC FUNCTIONAL GRAMMAR AND ITS CLASSROOM IMPLEMENTATION: A NATURALISTIC STUDY AT ENGLISH DEPARTMENT OF TIDAR UNIVERSITY - Winarsih, Dwi (Universitas Muhammadiyah Surakarta, 2013)
English language teaching in Indonesia which focuses on text types or genre. The teaching is based on the concept that language as a system of choice by which writers can communicate certain functions that allow them to express their experiences, to interact with others, and to create coherent message. Consequently, systemic functional grammar which views language as a strategic, meaning-making resource is implemented. However the facts show students of English Department have limited knowledge on it. Their average score is unsatisfactory, below 70. The objectives of the research are to describe (1) the students? mastery on interpersonal metafunction, experiential metafunction, and textual metafunction; and (2) to describe the classroom implementation of systemic functional grammar course. This naturalistic study is conducted at English Department. The subjects of this research are one lecturer and 30 students taking structure 3 course. Data are collected through classroom observation and relevant documentation. The result indicates that students? mastery of systemic functional grammar is low. They get confused when they come across with complex clauses in spoken text.